The effectiveness of visual intelligence strategy in the collection of students in the Department of Art Education in the perspective material: أسامة حسن عبد علي الصفار (Al-Academy, 2016)
Select the researcher discussed problem of asking the following : Do you use visual intelligence strategy effective in the collection of students in the Department of Art Education in the foreseeable material ? The research aims to " measure the effectiveness of the strategy in the collection of visual intelligence students in the Department of Art Education in the foreseeable material ". To verify the objective of this research was identify hypotheses zero to measure the level of achievement in the foreseeable material second grade students in the Department of Art Education - Faculty of Fine Arts . The population of the research students in the Department of Art Education / Faculty of Fine Arts at the University of Baghdad who are studying items scheduled perspective within vocabulary curriculum Department of Technical Education 's ( 109 ) students , distributors (6) people. Akhtar researcher discussed random sample of second grade students - Division (a) of the Department of Art Education and both sexes , were selected ( 10 ) students who are studying perspective on the material in accordance with the visual intelligence strategy . The researcher used the experimental design is the same group ( experimental sample per ) to verify the objectives of the research as it aims Current search to reveal the effectiveness of the Strategy intelligence visual in the collection of students in the Department of Art Education in the material perspective for the purpose of achieving the objectives of the research and hypotheses it was necessary to create the requirements of research and whose required educational material that have been taught during the application of research and experience , which was distributed on two and lessons within two weeks. Subject of the first lesson ( the third dimension of forms and objects) The theme of the second lesson is ( Record peace ) After determining the educational material , select the educational objectives of the researcher thus refers to the behavioral goals . The researcher building objective test type ( multiple-choice ) consists of (20) paragraph and to show search results used means statistical represented (b test and Caucasians "Wilcoxon" to show the result of the null hypothesis specified in current research and achieve the goal of research and equation Keodr Richardson -20Kauder Richardson -20 " " used to find reliability coefficient cognitive achievement test . The most important findings of the researcher and that can be summarized in the following points :The calculated value less than a small spreadsheet to show the presence of statistically significant differences at the level of significance ( 0.05 ) to favor the achievement test post so first rejected the null hypothesis "there is no statistically significant differences at the level of significance (0.05) between the average scores of the collection experimental group students ( who are studying perspective on the material according to the visual intelligence strategy ) in the pre and post tests . " And thus accept the null hypothesis second alternative It is clear that the experimental group students who have studied the material according to intelligence strategy perspective demonstrated excellence in visual post-test results compared to the results of pre – test. The researcher has recommended a set of recommendations including:1 - emphasis on methods and strategies for teaching modern in the field of education and training of cadres of teachers for the use of such methods in their field and the emphasis on a strategy of multiple intelligences and in particular strategic intelligence visual because they show the strengths and weaknesses of the students and to reach the desired goals in the educational process .2 - tendencies interest of students and diversification of activities where they are interested in the detection of their intelligence and help them in their development . To complement aspects of current research researcher suggest the following :1 - the effectiveness of an educational program in the development of multiple intelligences among third-year students in the Department of Art Education in Article Creation imaging .2 - the effectiveness of multimedia programs prepared in the light of the theory of multiple intelligences different thinking patterns in the foreseeable material